2022
DOI: 10.35848/1347-4065/ac5fc8
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic luminescence-downshifting effects of Zn-based Mn-doped nanoparticle layers on Si solar cells

Abstract: Luminescence downshifting (LDS) effects of Zn-based Mn-doped nanoparticles (NPs) on characteristics of Si solar cells are investigated. ZnSe:Mn/ZnS core-doped core/shell NPs and ZnSe/ZnS:Mn/ZnS shell-doped core/shell/shell NPs are deposited on glass plates using layer-by-layer method. It is found that shell-doped NPs are superior as LDS materials by measuring their optical properties. We deposit LDS layers made of shell-doped NPs on Si cells and measure their internal quantum efficiencies (IQEs) to examine LDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…It was reported that NPs were periodically aligned in LBLbased LDS films. 39) The in-plane and out-of-plane separations between the centers of 5 nm NPs are estimated to be 5 and 5.5 nm, respectively, which means that the number density of NPs in a 140 nm thick LBL-based LDS film, which we previously reported, 28) is 6.0 × 10 18 cm −3 . Given that the IOD of this LDS film was 0.07 at 350 nm, the extinction coefficient at 350 nm was 3.30 × 10 −2 .…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…It was reported that NPs were periodically aligned in LBLbased LDS films. 39) The in-plane and out-of-plane separations between the centers of 5 nm NPs are estimated to be 5 and 5.5 nm, respectively, which means that the number density of NPs in a 140 nm thick LBL-based LDS film, which we previously reported, 28) is 6.0 × 10 18 cm −3 . Given that the IOD of this LDS film was 0.07 at 350 nm, the extinction coefficient at 350 nm was 3.30 × 10 −2 .…”
Section: Discussionmentioning
confidence: 78%
“…IQE of cells coated with LDS films in the UV wavelength region are be given by the sum of contributions of incident UV photons and downshifted photons emitted from NPs, i.e. IQE of cells coated with LDS films at 350 nm, IQE 350,NP , is expressed as, 28) 28) 140 nm 0.07 3.30 × 10 −2 6.0 × 10 18 cm −3 SK1005-5…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations